Generation of XML representation from UML generalization structure - Wong, Swee Yin (Universiti Malaysia Sarawak, (UNIMAS), 2015)
Unified Modeling Language(UML) is a standard object-oriented design modeling language to define a software system in industry. It is economic and ease of use, but it is not reliable. Wghile for Vienna Development Method (VDM++). even though it is expensive and difficult to be used, but it is reliable. Integration of UML and VDM++ can rpoduce an economic and reliable model. Yet, they are unable to communicate with each other due to their different semantics and syntax.